Stationarity Properties of Renewable Energy Consumption in the Commonwealth of Independent States - Yasar, Nermin (International Journal of Energy Economics and Policy, 2019)
This study investigates the stochastic properties of renewable energy consumption series across 11 Commonwealth of Independent States countries through the period of 1990-2015. For this purpose, along with traditional stationarity analysis recently improved unit root techniques which allows for nonlinear adjustments in the data generating process are used in this paper. Based on our findings we may conclude that, consideration of nonlinearity in regression process causes to more frequent non rejection of the null hypothesis of stationarity. It implies that ignoring possible nonlinearities in time series regression process may lead to some misleading results. Hereby, fluctuations in global energy supply and trade systems influence renewable energy consumption in nonlinear pattern and policy-makers should take it into consideration in terms of proper energy policy implication. Keywords: Renewable energy consumption, Panel Unit Root, Nonlinearity, ESTAR Panel Unit Root JEL Classifications: C22, Q20, P28 DOI: https://doi.org/10.32479/ijeep.8617